(untitled) (CIPEEX, 2025)
Introduction: The integration of palliative care into Primary Health Care (PHC) is essential to expand humanization and comprehensiveness within the Brazilian Unified Health System (SUS), especially for patients with serious or chronic life-threatening illnesses. Due to its capillarity, PHC allows for the early detection of such cases and the provision of continuous care. However, even with the National Policy on Palliative Care (PNCP), theoretical and practical gaps persist that hinder its effectiveness. This study aims to assess the importance of integrating palliative care into Brazilian PHC. Methods: This study is a literature review. Articles were searched in the LILACS, PubMed, and SciELO databases, using the descriptors “Palliative Care,” “Primary Health Care,” “Medical Education,” and “Comprehensive Health Care,” connected with the Boolean operator “AND.” Studies published in Portuguese, English, and Spanish, without time restrictions, that addressed the connection between palliative care and PHC were included. Results: National and international literature reveals that the early and multiprofessional introduction of palliative care leads to significant improvements in the quality of life of patients and families, in addition to reducing unnecessary hospitalizations and additional costs for health systems. In the community context, PHC represents a favorable environment for home-based care, promoting comfort, dignity, and stronger relationships with the health care team. However, challenges remain, such as the lack of qualified teams, the absence of clear protocols, and deficiencies in medical training on palliative care. These factors undermine the effectiveness of the PNCP and make it more difficult to establish a sustainable policy within PHC. Conclusion: The implementation of palliative care in PHC should be regarded not only as a clinical guideline but also as an ethical, social, and strategic requirement to strengthen comprehensiveness in SUS. To achieve this, it is essential to invest in continuous training of health teams, develop well-defined protocols for identification and referral, and recognize palliative care as a fundamental right inseparable from comprehensive health care.